Family Function, Loneliness, Emotion Regulation, and Hope in Secondary Vocational School Students: A Moderated Mediation Model - Yun, Pan; Xiaohong, Han; Zhongping, Yang; Zhujun, Zhao (Frontiers in Public Health, 2021)
This study explored family function as a key factor of loneliness, hope, and emotion related to secondary vocational school students during the novel coronavirus pandemic. Chinese versions of the Olson Family Function Scale, Russell Loneliness Scale, Snyder Hope Scale, and Gross Emotion Regulation Scale were completed by 5,138 participants. Guardian type significantly predicted family function and loneliness. Family function significantly and positively correlated with loneliness. The relationship between family function and loneliness was mediated by hope, and expressive suppression concurrently moderated the relationship between hope and loneliness. Our study offers meaningful insights into the family function of Chinese secondary vocational school students. The findings supported a moderated mediation model that exemplifies the relationship between family function, loneliness, expressive suppression, and hope. Although the results showed that high hope mediated lower family functioning and loneliness, low expressive suppression led to intense loneliness immediately. This study confirms that emotional strategy is important and associated with mental health. It also suggests that schools should pay more attention to students’ emotion regulation and help them rebuild hope or appropriate cognition to relieve loneliness during crisis events.